Therapeutic target exploration of Shugan Jianpi formula in liver fibrosis: an integrated lncRNA-mRNA co-expression network analysis - Kaiqiang Wan; Qiong Zhou; Ruirui Feng; Chang Fan; Weibing Shi; Wenbin Xu; Hui Jiang; Qiumei Zhou (Molecular Genetics and Genomics, 2026)

Long-term fertilization enhances Bacilli cell size by increasing soil resource availability and shifting its metabolic strategies - Nan Rong; Youzhi Feng; Ruirui Chen; Yuanyuan Bao; Shiying He; Shudong Ding; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2026)

Nano Fe-C3N4-enhanced hydroxyl radical loop promotes organic matter decomposition in anoxic soils - Jian Chen; Ruirui Chen; Huan Deng; Jan Dolfing; Yifan Zhang; Xu Song; Shiying He; Yuanyuan Bao; Youzhi Feng (Journal of Environmental Chemical Engineering, 2026)

Historical grazing intensity determines the response patterns of plant community and soil nutrient stocks to grazing exclusion in a temperate meadow steppe - Haonan Guo; Xiaoping Xin; Jiquan Chen; Phil J. Murray; Maira Kussainova; Wei Fang; Zhigang Zhao; Hui Li; Cuixia Jiang; Yufan Si; Amarjargal Amartuvshin; Alim Pulatov; et al. (Agriculture, Ecosystems & Environment, 2026)

PEN: Carbon-induced nitrogen pumping by microorganisms in soil - Xiaoting Wang; Ruirui Chen; Youzhi Feng; Emad M. Hafez; Yakov Kuzyakov (Applied Soil Ecology, 2026)

Rewiring (p)ppGpp metabolism for high-yield anaerobic methanol and CO2 conversion in Butyribacterium methylotrophicum - Yuanke Guo; Feiyi Zhuang; Rui Zhang; Ruirui Qin; Jiao Feng; Kequan Chen; Xin Wang (Chemical Engineering Journal, 2026)

Changes in plant community composition and soil resource drive jointly fine root productivity response to grazing in a meadow steppe - Hui Li; Changliang Shao; Yuguang Ke; Xiaoping Xin; Ziwei Tao; Yufan Si; Haonan Guo; Cuixia Jiang; Ruirui Yan; Guozhen Du; Zihao Li; Feng Liu (Plant and Soil, 2026)

Corrigendum to “Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region” [Sci. Total Environ. 946 (2024) 174054] - Xiaoping Xin; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; Ruirui Yan; et al. (Science of The Total Environment, 2025)

Facile synthesis of mesoporous In2O3-CexZr1-xO2 catalysts for efficient CO2 electroreduction to formate - Ruirui Qi; Manfen Liang; Weisong Feng; Weijie Zhou; Xiangyang He; Mei Wu; Haimei Xu; Zhichao Miao (Journal of Environmental Chemical Engineering, 2025)

Novel alkali-resistant nitrogen and phosphorus removal strain I4: Performance evaluation and molecular mechanism - Xiaoxuan Fan; Jiayi Zhou; Qionghua Chen; Yuwei Feng; Ruirui Han; Guangfeng Chen; Sha Yue; Yonghao Ma; Hu Shu (Bioresource Technology, 2025)

National-scale genomic diagnosis of rare diseases in China - Xiaodong Luan; Ye Jin; Liping Guan; Peng Liu; Hailong Feng; Dingding Zhang; Jingdan Chen; Weida Liu; Fangyuan Li; Anqi Wang; Kun Zhao; Ruirui He; et al. (Science Bulletin, 2025)

A multi-sensor, phenology-based approach framework for mapping cassava cultivation dynamics and intercropping in highly fragmented agricultural landscapes - Xincheng Wang; Qinfei Wang; Hongyan Lai; Zhenwen Zhang; Ting Yun; Xiaojing Lu; Guizhen Wang; Shangye Lao; Qi Liao; Saiqing Lu; Ruirui Chen; Shijing Fang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A comprehensive investigation of mechanical mixing-thermal activation for CaO-based adsorbent with coal fly ash as a stabilizer - Ruirui Zhang; Xuehua Shen; Yongjia Liang; Han Hua; Gang Li; Feng Yan; Zewei Quan; Zuotai Zhang (Chemical Engineering Journal, 2025)

Large electrocaloric temperature change in lead-free (Bi0.47Na0.47Ba0.06)TiO3-based ceramics via regulating non-ergodic - ergodic transition - Junwen Mei; Mei Bai; Yangfei Gao; Ruirui Kang; Xiangran Pei; Haichao Hu; Junjie Xiong; Jiantuo Zhao; Feng Li; Dezhen Xue; Zhongliang Lu; Xiaojie Lou (Chemical Engineering Journal, 2025)

Antifungal immunity: advances in PRR recognition, adaptive responses, and immune-based therapies - Jianlin Zhou; Xueni Lu; Ruirui He; Yanyun Du; Bo Zeng; Lingyun Feng; Ming Yi; Yuan Wang; Chenhui Wang (Science China Life Sciences, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

Highly synergistic degradation of norfloxacin and outstanding elimination of antibiotic-resistant elements by a combined electro-Fenton/peracetic acid process under mild conditions - Ling Feng; Wentao Dong; Bowei Li; Qing Li; Zhijing Liu; Ruirui Feng; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2025)

Warmer summers have the potential to affect food security by increasing the prevalence and activity of Actinobacteria - Yuanyuan Bao; Jan Dolfing; Zhiying Guo; Jie Liu; Xianzhang Pan; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Lixia Zhang; Ruirui Chen; Xin Li; Youzhi Feng (European Journal of Soil Biology, 2025)

Transcriptome-Wide Analysis Revealed the Influential Role of PbrMTP (Metal Tolerance Protein) in the Growth and Fruit Development of Chinese White Pear - Ruirui Xu; Ahmad Ali; Ying Li; Xiao Zhang; Rahat Sharif; Xinxin Feng; Baopeng Ding (Journal of Plant Growth Regulation, 2025)

Hydrogen-rich water enhanced salt tolerance in tomato seedlings by regulating strigolactone biosynthesis genes SlMAX1 and SlD27 - Fujin Ye; Hua Fang; Li Feng; Meimei Shi; Ruirui Yang; Weibiao Liao (Plant and Soil, 2025)

Phosphorus Cycling as a Function of Soil Microbiome - Youzhi Feng; Ruirui Chen (Global Change Biology, 2024)
Phosphorus (P), especially its availability, plays a pivotal role in the productivity of terrestrial ecosystems. The recent article makes several key discoveries with substantial implications for understanding the global soil P cycling as a function of microbiome and ecological effects of human activities.

Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region - Xiaoping Xin; Xueqi Lan; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; et al. (Science of The Total Environment, 2024)

Lithium-ion battery remaining useful life prediction: a federated learning-based approach - Ruirui Zhong; Bingtao Hu; Yixiong Feng; Shanhe Lou; Zhaoxi Hong; Fei Wang; Guangshen Li; Jianrong Tan (Energy, Ecology and Environment, 2024)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

The ripple effects of international energy prices on domestic products in China under external shocks - Yue Ma; Ling Miao; Lianyong Feng; Ruirui Fang (Environment, Development and Sustainability, 2024)

Unearthing the global patterns of cultural heritage microbiome for conservation - Yongjie Yu; Jianwei Zhang; Ruirui Chen; Claudia Coleine; Wenjing Liu; Manuel Delgado-Baquerizo; Youzhi Feng (International Biodeterioration & Biodegradation, 2024)

Large room-temperature electrocaloric response achieved by tailoring the first-order orthorhombic-tetragonal phase transition in BaTiO3-based ferroelectric ceramics - Ruirui Kang; Wenjing Qiao; Junjie Xiong; Haichao Hu; Ming Wu; Feng Li; Yangfei Gao; Lixue Zhang; Yingying Zhao; Xiaojie Lou (Chemical Engineering Journal, 2024)

Urban green space area mitigates the accumulation of heavy metals in urban soils - Shuhong Luo; Ruirui Chen; Jigang Han; Weiwei Zhang; Evangelos Petropoulos; Yun Liu; Youzhi Feng (Chemosphere, 2024)

Isolation methods, proliferation, and adipogenic differentiation of adipose-derived stem cells from different fat depots in bovines - Ruirui Zhu; Ye Feng; Ruirui Li; Kelong Wei; Yun Ma; Qingyou Liu; Deshun Shi; Jieping Huang (Molecular and Cellular Biochemistry, 2024)

Bacterial interference competition and environmental filtering reduce the fungal taxonomic and functional contribution to plant residue decomposition in anoxic paddy soils - Yuanyuan Bao; Jan Dolfing; Xin Li; Ruirui Chen; Xiaodan Cui; Zhongpei Li; Xiangui Lin; Youzhi Feng (Soil and Tillage Research, 2024)

Effects of oyster shells on maturity and calcium activation in organic solid waste compost - Wanlin Song; Yang Zeng; Jiali Wu; Qian Huang; Ruirui Cui; Derui Wang; Yuxue Zhang; Min Xie; Dawei Feng (Chemosphere, 2023)

Root-derived C distribution drives N transport and transformation after 13C and 15 N labelling on paddy and upland soils - Xiaoting Wang; Ruirui Chen; Evangelos Petropoulos; Bingqian Yu; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2023)

Administration of necrostatin-1 ameliorates glucocorticoid-induced osteonecrosis of the femoral head in rats - Min Feng; Ruirui Zhang; Mingming Zhang; Ming Chen; Le Ji; Dapeng Duan; Hui Qiang (Journal of Molecular Histology, 2023)

Trade-off between microbial ecophysiological features regulated by soil fertility governs plant residue decomposition - Yuanyuan Bao; Jan Dolfing; Ruirui Chen; Zhongpei Li; Xiangui Lin; Youzhi Feng (Soil and Tillage Research, 2023)

Spatial–temporal dynamics of the built environment toward sustainability: A material stock and flow analysis in Chinese new and old urban areas - Dong Yang; Mengyuan Dang; Jing Guo; Lingwen Sun; Ruirui Zhang; Feng Han; Feng Shi; Qian Liu; Hiroki Tanikawa (Journal of Industrial Ecology, 2023)
The urban built environment has accumulated massive amounts of resources, which is the main “hot spot” of construction materials and energy consumption in cities. To effectively monitor and manage resources use and waste disposal toward sustainability, this study intended to explore different metabolic paths of the urban built environment, as well as strategies for new and old urban areas separately with the help of material stock and flow analysis. Based on snapshots of 2003, 2010, and 2017 and combined with big data, a four‐dimensional geographic information system buildings database of Lixia District in Jinan, China, was compiled for bottom‐up stock modeling. Finally, the environmental impact assessment of the buildings’ demolition and disposal stage was carried out. The results showed that the building material stock was 142.31 Mt in 2017, with an increase of 69% from 2003. The reinforced concrete buildings increased rapidly from 2003 to 2017, especially in new urban areas, which has boosted demand for steel and cement by more than 150% during these 15 years. The material stock of the old urban area tends to be saturated, whereas the new urban area has experienced a rapid expansion with the material inflow four times as large as the material outflow. Potential recycling of waste concrete can reduce the generation of building demolition waste by 50%, save 0.15 km 2 of land occupation, increase raw material substitution by nearly 10 times, and reduce CO 2 emissions by 2.5 times.

What matters most to the material intensity coefficient of buildings? Random forest‐based evidence from China - Ruirui Zhang; Jing Guo; Dong Yang; Hiroaki Shirakawa; Feng Shi; Hiroki Tanikawa (Journal of Industrial Ecology, 2022)
Material intensity coefficient (MIC) is vital for material stock accounting in the field of industrial ecology. However, the categorization of MIC varies across regions especially for buildings that diverge greatly along the history and space aspect, and acquisition of MIC data and building information have always been a challenge in related studies. In this study, the state‐of‐art ensemble model “Random Forest” was developed on Chinese buildings to identify the impact of four building attributes (building structure, construction year, use type, and region) on MIC, and these features’ importance was further assessed by considering variable correlations. The features’ importance and their individual effects on MIC were intuitively revealed by depicting the partial dependence plots. Finally, a set of hierarchical MIC values was estimated by integrating the order of four variables’ importance and a quick MIC calculator was provided. Results showed that building structure is the most influential attribute for MIC, followed by the construction year, use type, and region, successively. The RF‐based MIC values allow researchers to apply it to material stock and flow analysis by choosing a specific building feature(s) in the MIC calculator, which is (are) available in building physical inventory data. This study provides a method that could help researchers locate key influencing variables and give insights into the comparability of MIC research across regions and play an important role in developing urban mining and circular economy strategies.

Balanced stochastic versus deterministic assembly processes benefit diverse yet uneven ecosystem functions in representative agroecosystems - Wenjing Liu; Emily B. Graham; Yang Dong; Linghao Zhong; Jianwei Zhang; Chongwen Qiu; Ruirui Chen; Xiangui Lin; Youzhi Feng (Environmental Microbiology, 2021)
Summary Ecological assembly processes, by influencing community composition, determine ecosystem functions of microbiomes. However, debate remains on how stochastic versus deterministic assembly processes influence ecosystem functions such as carbon and nutrient cycling. Towards a better understanding, we investigated three types of agroecosystems (the upland, paddy, and flooded) that represent a gradient of stochastic versus deterministic assembly processes. Carbon and nutrient cycling multifunctionality, characterized by nine enzymes associated with soil carbon, nitrogen, phosphorous and sulfur cycling, was evaluated and then associated with microbial assembly processes and co‐occurrence patterns of vital ecological groups. Our results suggest that strong deterministic processes favour microorganisms with convergent functions (as in the upland agroecosystem), while stochasticity‐dominated processes lead to divergent functions (as in the flooded agroecosystem). To benefit agroecosystems services, we speculate that it is critical for a system to maintain balance between its stochastic and deterministic assembly processes (as in the paddy agroecosystem). By doing so, the system can preserve a diverse array of functional traits and also allow for particular traits to flourish. To further confirm this speculation, it is necessary to develop a systematic knowledge beyond merely characterizing general patterns towards the associations among community assembly, composition, and ecosystem functions.

Functional community composition has less environmental variability than taxonomic composition in straw-degrading bacteria - Yuanyuan Bao; Zhiying Guo; Ruirui Chen; Meng Wu; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2020)

Effects of different inhibitors such as malonic acid, Na3PO4 and HgCl2 on uptake of different forms of antimony in rice plant - RenWei Feng; Lei Lei; BiXiu Liu; WenXiang Chen; RuiRui Zhang; LiZhen Wang; YuanPing Li; JunMing Su; JiaXin Dai; RenJie Wang; ZiTing Lin; Ibtissem Ben Fekih; et al. (Plant and Soil, 2019)

Bacterial communities involved directly or indirectly in the anaerobic degradation of cellulose - Yuanyuan Bao; Jan Dolfing; Baozhan Wang; Ruirui Chen; Miansong Huang; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2019)

Mapping daily leaf area index at 30 m resolution over a meadow steppe area by fusing Landsat, Sentinel-2A and MODIS data - Zhenwang Li; Chengquan Huang; Zhiliang Zhu; Feng Gao; Huan Tang; Xiaoping Xin; Lei Ding; Beibei Shen; Jinxun Liu; Baorui Chen; Xu Wang; Ruirui Yan (International Journal of Remote Sensing, 2018)

Two key features influencing community assembly processes at regional scale: Initial state and degree of change in environmental conditions - Youzhi Feng; Ruirui Chen; James C. Stegen; Zhiying Guo; Jianwei Zhang; Zhongpei Li; Xiangui Lin (Molecular Ecology, 2018)
Belowground microbial communities strongly influence ecosystem function such that predicting function may rely on understanding ecological processes that assemble communities. Uncertainty remains, however, in what governs the relative contributions of different ecological processes. To help fill this knowledge gap, we test the general hypothesis that both initial state and degree of change in environmental conditions govern the relative contributions of different ecological assembly processes. To do so, we leveraged regional‐scale nutrient and organic matter addition experiments and used soil organic matter (SOM) as a proxy of integrated soil environmental conditions. Consistent with our hypothesis, we found that both the initial amount of SOM and the degree of change in SOM—in response to nutrient addition—influenced the relative contributions of different ecological assembly processes. These influences were most clearly observed at the regional scale, suggesting potential scale dependence. More specifically, nutrient additions homogenized bacterial community composition due to enhanced influences of homogenizing dispersal when SOM content was initially high. In contrast, nutrient additions led to divergence in community composition due to variable selection when initial SOM was low and/or when SOM increased significantly in response to nutrient additions. Our findings indicate important connections among initial conditions, degree of change in environmental variables and microbial community assembly processes that may influence ecosystem processes. These conceptual inferences highlight a need to strengthen connections between ecological theory and biogeochemical modelling.

Application of the CRISPR/Cas9 system in Dioscorea zingiberensis - Shan Feng; Wei Song; Ruirui Fu; Hong Zhang; Anran Xu; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)